2021–2022 Florida Citrus Production Guide: Soft-Bodied Insects Attacking Foliage and Fruit - Lauren Marie Diepenbrock; Lukasz L. Stelinski; Xavier Martini; Jawwad Qureshi (EDIS)
This publication was updated October 19, 2021 to state that chlorpyrifos tolerances will be revoked effective 2/28/22.